Block and Text Programming in Swedish High School: What do students know on their first day? - Snider, Johan; Bokström, Erik; Davidsson, Kasper; Eckerdal, Anna; Kastberg, Robin (2022 IEEE Frontiers in Education Conference (FIE), 2022)
This research work-in-progress paper presents findings related to upper secondary students’ understanding of programming concepts such as: (1) variable assignment, (2) if-statements, and (3) loops in Python and Scratch. In 2017, the Swedish education board added computer science curriculum to compulsory schooling. Students now entering upper secondary school are expected to have experience with programming. To find out how familiar first year upper secondary students are with programming, we assessed 172 students’ programming knowledge with a multiple choice questionnaire with block programming questions in Scratch and text programming questions in Python. Each question required students to read a program between 4-8 lines of code and correctly identify the output of the program. The questions included basic programming concepts such as: variable assignment, if-statements and loops. Additionally, we asked students to self-report their prior experiences with programming in terms of how many hours they had spent programming inside and outside of school, as well as if they had more experience with block or text programming. As expected, the students’ scores correlated positively with the amount of hours they self-reported to have spent programming inside and outside of school. In conclusion, we correlate students’ self-reported programming experience with their scores on the block and text sections and reason about these results based on teachers’ experience and research literature.